'This is what we've always wanted': Perspectives on young autistic people's transition from special school to mainstream satellite classes. (November 2019) - Croydon, Abigail; Remington, Anna; Kenny, Lorcan; Pellicano, Elizabeth
Background & aims: According to parents, teachers and policymakers alike, including autistic children and young people in mainstream schools is notoriously difficult – especially so for the significant minority of young people on the autism spectrum with additional intellectual, communication and behavioural needs. The current study sought to understand the perceived impact of one particular, emerging model of education, in which selected students from special schools are transferred to dedicated 'satellite' classes in local, mainstream partner schools, while continuing to receive the tailored curriculum and specialist teaching of the originating school. Methods: We conducted interviews with London-based young autistic people ( n = 19), their parents/carers and teachers to understand their experiences of transitioning from specialist to satellite mainstream provision. Results: Participants overwhelmingly welcomed the prospect of transition and its perceived benefits in the short and longer term. Young people and families celebrated achieving access to 'more normal places and things', 'seeing what others are doing', and greater autonomy, without losing the trusted expert support of their former special school. Young people also felt a deep sense of belonging to their new mainstream school, despite only being minimally included in regular mainstream classes and activities. Teachers were equally positive and felt that their students had responded to higher expectations in their new mainstream schools, reportedly resulting in better behavioural regulation and more sustained attention in the classroom. Conclusions: The strikingly positive evaluations provided by all participants suggest that this satellite model of education might have advantages for young autistic people with additional intellectual disability, when appropriate support extends across transition and beyond. Implications: These findings shed light on the experiences of an under-researched group of autistic students and a specific model of education – following a needs-based perspective on inclusion – that seeks to extend their participation in local schools. Future research should examine the potential effects of satellite classrooms on the knowledge of, and attitudes toward, autism in non-autistic mainstream peers.